Complementary Sex Determination in the Parasitic Wasp Diachasmimorpha longicaudata - Carabajal Paladino, Leonela; Muntaabski, Irina; Lanzavecchia, Silvia; Le Bagousse-Pinguet, Yoann; Viscarret, Mariana; Juri, Marianela; Fueyo-Sánchez, Luciana; Papeschi, Alba; Cladera, Jorge; Bressa, María José (PLOS ONE, 2015)
We studied the sex determination in Diachasmimorpha longicaudata, a parasitoid braconid wasp widely used as biological control agent of fruit pest tephritid flies. We tested the complementary sex determination hypothesis (CSD) known in at least 60 species of Hymenoptera. According to CSD, male or female development depends on the allelic composition of one sex locus (single-locus CSD) or multiple sex loci (multiple-locus CSD). Hemizygote individuals are normal haploid males, and heterozygotes for at least one sex locus are normal diploid females, but homozygotes for all the sex loci are diploid males. In order to force the occurrence of diploid males in D. longicaudata, we established highly inbred lines and examined their offspring using chromosome counting, flow cytometry, and sex ratio analysis. We found that when mother-son crosses were studied, this wasp produced about 20% of diploid males out of the total male progeny. Our results suggest that this parasitoid may represent the second genus with multiple-locus CSD in Hymenoptera. Knowledge about the sex determination system in D. longicaudata is relevant for the improvement of mass rearing protocols of this species. This information also provides the necessary background for further investigations on the underlying molecular mechanisms of sex determination in this species, and a better insight into the evolution of this pathway in Hymenoptera in particular and insects in general.